Browning‐Related Decreases in Water Transparency Lead to Long‐Term Increases in Surface Water Temperature and Thermal Stratification in Two Small Lakes. Issue 5 (23rd May 2018) - Pilla, Rachel M.; Williamson, Craig E.; Zhang, Jing; Smyth, Robyn L.; Lenters, John D.; Brentrup, Jennifer A.; Knoll, Lesley B.; Fisher, Thomas J.
Abstract: Surface water temperatures are warming in many lakes across the globe, and this is widely attributed to warming air temperatures. Yet two lakes in Pennsylvania (USA) have shown long‐term increases in surface water temperatures over the past 27 summers during a period with no significant increase in regional air temperature. We examined the relationship between long‐term trends in seven metrics of whole‐lake thermal structure in two lakes and several potential driver variables. Driver variables included water transparency, lake pH, and meteorological variables. Both lakes exhibited significant surface warming and hypolimnetic cooling, resulting in stronger thermal stratification that further reduced mixing and heat transfer to deep waters. During this time period, there were no long‐term trends in solar radiation or in thawing degree days, but annual precipitation and lake pH increased. Water transparency greatly decreased due to increased dissolved organic matter quantity and color, most likely due to increased precipitation and recovery from anthropogenic acidification. In both lakes, the changes in lake thermal structure and heat distribution were strongly related to the decreases in water transparency and increases in dissolved organic matter. This transparency‐mediated mechanism may augment the effects of air temperature‐driven lake warming in other regions where decreasing transparency is also prevalent, further enhancing increases in surface water temperature and thermal stratification. These results have important ecological and biogeochemical implications, highlighting the need for investigations of multiple drivers to fully understand how lakes will respond to future climate change. Plain Language Summary: Lakes provide key services to society ranging from drinking water and food to recreation and increased property value. But lakes are vulnerable to many environmental threats, including climate change. Two study lakes in Pennsylvania have experienced decreases in water clarity as the water has become more brown over the past three decades. As a result, sunlight and heat are more completely absorbed near the surface of the lake, with less light and heat reaching deeper waters. This leads to warmer surface waters and cooler deep waters. We attribute the reduced water clarity and changes in lake temperature to recovery from acid rain following the Clean Air Act amendments in the 1990s, combined with climate change‐induced increases in precipitation and storm events in the northeastern United States that increase runoff of organic matter into lakes. These changes are influencing other aspects of the lake ecosystem by accelerating oxygen depletion and altering the abundance of and habitat availability for algae, zooplankton, and fish. Key Points: Increases in dissolved organic matter and decreases in water transparency led to surface water warming and deep water cooling in two small temperate lakes Decreases in water transparency can lead to strong changes in lake thermal structure at rates similar to changes driven by warming air temperature The clear lake showed more pronounced changes in water transparency and in lake thermal structure compared to the darker lake